Investigação de propriedades quantitativas de relações simbólicas em quatro estudos experimentais envolvendo o paradigma de equivalência de estímulos - BORTOLOTI, Renato (2007)
This work presents four experimental studies that evaluated transfer of functions from faces expressing emotions to arbitrary figures equivalent to them. The specific goals of each study can be articulated around a proposal to investigate quantitative properties of equivalence relations. Chapter 1 describes an experiment conducted to examine if the level of transfer of functions can be affected by the delayed presentation of the comparison stimuli in a matching-to-sample training. In effect, the results showed more transfer when classes were trained with a delayed matching-to-sample procedure. The experiment presented in the Chapter 2 manipulated delayed matching and the number of stimuli intervening in the relation established among faces and figures. The increase in the number of intervenient stimuli negatively affected the formation of equivalence classes and reduced the transfer of function, but these effects were less pronounced when the relations were established by the delayed matching-to-sample procedure. Chapter 3 describes an experiment conducted to verify if arbitrary figures acquire properties from facial expressions presented always very quickly. In this condition, the transfer of functions occurred with less intensity than when the faces are presented for longer periods. Chapter 4 presents a study to evaluate the time spent by the participants to find arbitrary figures equivalent to certain facial patterns described as more quickly localized. Results replicated only in part the transfer of functions demonstrated in a previous experiment. The studies that compose this work provide evidence that the transfer of functions can suffer systematical variations according to the experimental parameters that are employed. Variations in the transfer of function indicate variations in the relatedness of equivalent stimuli.